Identification and Characterization of CYC-Like Genes in Regulation of Ray Floret Development in Chrysanthemum morifolium - Huang, Di (Front Plant Sci, 2016)
Chrysanthemum morifolium, one of the most economically important ornamental crops worldwide, is well-known for the elaborate and complex inflorescence which is composed of both bilaterally symmetrical ray florets and radially symmetrical disc florets. Despite continuing efforts, the molecular mechanisms underlying regulation of the two flower types are still unclear so far. CYC-like proteins have been shown to control flower symmetry or regulate flower-type identity in several angiosperm plant lineages. In this study, we conducted comparative analysis of the CmCYC2 genes in two chrysanthemum cultivars and their F1 progenies with various whorls of ray florets. Six CmCYC genes were identified and sequenced, all of which were grouped into the CYC2 subclade. All the six CmCYC2 genes were predominantly expressed in reproductive organs, and in particular in the petal of ray florets. Of these genes, the transcription level of CmCYC2c was highly up-regulated in ray florets of the double-ray flowered heads. In addition, the result that CmCYC2c was highly expressed at key developing stages indicates its role in regulating petal development. Furthermore, overexpression of CmCYC2c in C. lavandulifolium, one of the original species of C. morifolium, led to significant increase in flower numbers and petal ligule length of ray florets. Besides CmCYC2c, the expression of CmCYC2f was also significantly up-regulated in transgenic lines, implying a possible role in regulating development of ray florets. Both results of expression patterns and transgenic phenotypes suggest that CmCYC2c is involved in regulating ray floret identity in the chrysanthemum. This study will be useful for genetic manipulation of flower shape in chrysanthemum and hence promote the process of molecular breeding.